"Stay balanced" – effectiveness of evidence-based balance training for older adults transferred into a physical therapy primary care setting – a pilot study. Issue 13 (18th June 2020) - Palmgren, Anna; Ståhle, Agneta; Skavberg Roaldsen, Kirsti; Dohrn, Ing-Mari; Halvarsson, Alexandra
Abstract: Purpose: To evaluate the effects of the Stay Balanced program when this is transferred into a clinical setting regarding balance, gait speed, leg muscle strength, concerns about falling, and physical activity. Method: Implementation pilot study with a pre-post intervention design. Fifteen older adults, 75–91 years of age, participated in a progressive balance training program with a focus on divided attention. The balance training was performed in group sessions twice a week for 10 weeks at a primary care physical therapy clinic. Training efficacy was evaluated after completion of training as well as after 3 months using the Mini-Balance Evaluation Systems Test (Mini-BESTest), 10-meter walk test, 30-s chair stand test, Fall Efficacy Scale-International (FES-I), and steps/day. Results: Significant improvements were shown at the 10-week follow up for balance, gait speed, leg muscle strength, and concerns about falling ( p  < 0.008). At the 3-month follow-up balance, leg muscle strength and concerns about falling showed persistent improvement compared to baseline ( p  < 0.045). No significant differences were found for physical activity. Conclusions: This study confirms the results of our previous randomized controlled trials (RCTs), and suggests that the Stay Balanced program can be transferred to clinical physiotherapy practice. The program was appreciated by the participants and proved to be safe, effective, and feasible in primary care. Implication for rehabilitation: The Stay Balance program can easily be transferred to clinical practice without losing the effectiveness of the intervention in older adults with balance problems. The program was appreciated by the participants and proved to be safe, effective, and feasible when executed in primary care. Stay Balance program is an individually adjusted and progressive group balance training including exercises with divided attention that can easily be transferred to tasks in daily life.